PENGARUH KEBIJAKAN HUTANG DAN PERTUMBUHAN PENJUALAN TERHADAP PERTUMBUHAN LABA PADA PT LINK NET TBK PERIODE 2015-2024 - Hilda Destiana Putri; Nurwita Nurwita (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2026)
This study aims to examine the effect of Debt Policy and Sales Growth on Profit Growth at PT Link Net Tbk during the period 2015–2024, both partially and simultaneously. The research employs a quantitative method with an associative approach. The population consists of the financial statements of PT Link Net Tbk for the period 2015–2024, while the sample is derived from balance sheet and income statement data for the same period. Data were collected by downloading the company’s financial statements from the official website. The data analysis techniques include descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, correlation analysis, coefficient of determination analysis, and hypothesis testing. The results show that partially, Debt Policy measured by the Debt to Asset Ratio (DAR) has a positive and significant effect on profit growth. Meanwhile, Debt Policy measured by the Debt to Equity Ratio (DER) has a negative and significant effect on profit growth. Sales Growth does not have a significant effect on profit growth. Simultaneously, Debt Policy and Sales Growth have a significant effect on Profit Growth. The coefficient of determination value of 0.912 indicates that 91.2% of profit growth can be explained by Debt Policy and Sales Growth, while the remaining 8.8% is influenced by other variables not examined in this study